2006
DOI: 10.1021/jm050901o
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Wortmannin and 17-Hydroxywortmannin Conjugates as Phosphoinositide 3-Kinase Inhibitors Active in Human Tumor Xenograft Models

Abstract: Phosphoinositide 3-kinase (PI3K) is an important target for cancer chemotherapy due to the deregulation of its signaling pathway in a wide spectrum of human tumors. Wortmannin and its analogues are potent PI3K inhibitors whose therapeutic use has been impeded by inherent defects such as instability and toxicity. Pegylation of wortmannin and 17-hydroxywortmannin gives rise to conjugates with improved properties, including a higher therapeutic index. Pegylated 17-hydroxywortmannin (8, PWT-458) has been selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
(42 reference statements)
0
28
0
Order By: Relevance
“…The self-activating viridin prodrug undergoes slow self activation to release low and sustained levels of NBD-wortmannin (48, 49), increasing its potency. Wortmannin is a potent inhibitor of PI3K and other kinases (50)(51)(52)(53). Therefore, in light of the beneficial effects of PI3K inhibitors in models of inflammatory disorders (54), we tested the self-activating viridin prodrug directly in vivo, as we had done with dexamethasone.…”
Section: Resultsmentioning
confidence: 99%
“…The self-activating viridin prodrug undergoes slow self activation to release low and sustained levels of NBD-wortmannin (48, 49), increasing its potency. Wortmannin is a potent inhibitor of PI3K and other kinases (50)(51)(52)(53). Therefore, in light of the beneficial effects of PI3K inhibitors in models of inflammatory disorders (54), we tested the self-activating viridin prodrug directly in vivo, as we had done with dexamethasone.…”
Section: Resultsmentioning
confidence: 99%
“…Although preclinical studies showed Wtmn was an extremely effective radiosensitizer, its clinical translation was limited by poor solubility, low stability, and high toxicity (3)(4)(5)(6)(7)(8). Since its discovery more than four decades ago, many Wtmn analogs have been developed to improve on the stability and pharmacologic properties of Wtmn (9)(10)(11). Today, only one Wtmn analog, PX-866, remains under clinical investigation (12).…”
mentioning
confidence: 99%
“…Various modifications and conjugations with wortmannin have been reported, establishing it as an effective antitumor agent. 16,27 However, in the present study, the direct apoptotic effect of wortmannin at various concentrations was investigated selectively in the MCF-7 cell line. Thus, the primary goal of these experiments was to determine the apoptotic effects of wortmannin in a widely used MCF-7 cell model.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, mutated PI3K activation is abnormally expressed or overexpressed in several cancers, including stomach, colon, breast, lung, ovarian, and pancreatic cancer, with activation of its main downstream gene, Akt. 11,16,17 A study has concluded that PI3K-Akt plays a major role in this cell line with regard to increased drug resistance. 18,19 Deregulated PI3K-Akt activity has also been reported in breast malignancies associated with increased resistance to multiple chemotherapeutics and radiotherapies.…”
Section: Introductionmentioning
confidence: 99%